(untitled) (Groundings Undergraduate, 2023)
Singapore’s relationship with colonialism has long been fraught with resentment while simultaneously being unable to detach itself from its identity as a former British colony. Colonial officer Sir Stamford Raffles is regarded as a national icon, after whom the Raffles Hospital, Raffles Institution and business district Raffles Place are named after. Along the Singapore River is a white marble statue of Raffles, with the plaque reading “On this historic site, Sir Thomas Stamford Raffles first landed in Singapore on 28th January 1819, and with genius and perception changed the destiny of Singapore from an obscure fishing village to a great seaport and modern metropolis.” Yet, there have been efforts to counter Western influence in Singapore, to justify illiberal or anti-democratic policies or simply to cultivate a synthetic national identity amongst a majority immigrant population with no primordial connection to the land. It is then necessary to investigate the origins of this strange relationship with the British: a desire to either defend the colonists or to declare Western values as wholly irreconcilable to ours, and therefore need to be rejected.